The association between hourly systolic blood pressure variability and outcomes in patients with intracerebral hemorrhage is time-dependent: post-hoc analysis of the ATACH-2 trial - Qureshi, Adnan; Baskett, William; Gomes, Joao A.; Lakhani, Pashmeen; Rabinstein, Alejandro A.; Rose, David Z.; Suarez, Jose I.; Steiner, Thorsten; Shyu, Chi-Ren (Neurocritical care, 2025)
Systolic blood pressure (SBP) variability has been associated with an increase in rates of death or disability in patients with intracerebral hemorrhage (ICH). We analyzed data from the Antihypertensive Treatment of Acute Cerebral Hemorrhage (ATACH)-2 trial to determine whether the association between SBP variability and death or disability at 90 days is dependent on the time from randomization.